2018
DOI: 10.1128/aem.01038-18
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal Concentrations in a Coastal Ecosystem Are a Function of Fecal Source Input, Environmental Conditions, and Environmental Sources

Abstract: Fecal pollution at coastal beaches requires management efforts to address public health and economic concerns. Feces-borne bacterial concentrations are influenced by different fecal sources, environmental conditions, and ecosystem reservoirs, making their public health significance convoluted. In this study, we sought to delineate the influences of these factors on enterococcal concentrations in southern Maine coastal recreational waters. Weekly water samples and water quality measurements were conducted at fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 68 publications
1
11
0
1
Order By: Relevance
“…This has led regulatory agencies to require implementation of watershed management programs to reduce FIB concentrations in surface waters. However, numerous efforts have shown that identifying point and non-point sources of these organisms is challenging (Nix et al, 1993;Goodwin et al, 2017), particularly because natural growth and persistence of FIB in sediments may constitute a significant source of organisms (Crabill et al, 1999;Cinotto, 2005;Pachepsky and Shelton, 2011;Rothenheber and Jones, 2018). Therefore, the resulting lack of ability to reduce FIB concentrations and loads hinders the development, implementation and enforcement of strategies to prevent, mitigate and recover from episodic and/or chronic fecal contamination, and to meet water quality standards [He et al, 2007;Rowny and Stewart, 2012;New Mexico Environment Department (NMED), 2018].…”
Section: Introductionmentioning
confidence: 99%
“…This has led regulatory agencies to require implementation of watershed management programs to reduce FIB concentrations in surface waters. However, numerous efforts have shown that identifying point and non-point sources of these organisms is challenging (Nix et al, 1993;Goodwin et al, 2017), particularly because natural growth and persistence of FIB in sediments may constitute a significant source of organisms (Crabill et al, 1999;Cinotto, 2005;Pachepsky and Shelton, 2011;Rothenheber and Jones, 2018). Therefore, the resulting lack of ability to reduce FIB concentrations and loads hinders the development, implementation and enforcement of strategies to prevent, mitigate and recover from episodic and/or chronic fecal contamination, and to meet water quality standards [He et al, 2007;Rowny and Stewart, 2012;New Mexico Environment Department (NMED), 2018].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that antibiotic resistance genes were acquired by multiple separate acquisition events mediated by plasmids (Villa et al, 2012;Voulgari et al, 2014). The occurrence of plasmids raises concerns about the possibility of the detected strains contributing to the dissemination of resistance genes among bacterial species in the water environment (Cloutier and McLellan, 2017;Rothenheber and Jones, 2018;Schang et al, 2016). Vancomycin-resistant enterococci were not detected in any of the water samples.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IE and TTC concentrations is not a rule. It has been shown that the concentrations of enterococci in the coastal estuarine/marine beach study area were largely controlled by particle-associated enterococci and mammal fecal source input ( Rothenheber and Jones, 2018 ). The human-specific marker indicates that contamination was of human origin.…”
Section: Discussionmentioning
confidence: 99%